A novel dynamic simulation model for the thermo-economic analysis and optimisation of district heating systems. (15th September 2020) - Barone, G.; Buonomano, A.; Forzano, C.; Palombo, A.
Highlights: Development of a plug-flow model for dynamic thermal behaviour of district heating. Comprehensive study of a district heating supplied by combined heat and power plant. Optimization of the pipes network diameter of the entire district heating. Parametric analysis for the economic optimization of the entire system power plant. Energy savings (11.7 GWh/y), and avoided carbon dioxide (16.1 ktCO2 /y) Abstract: This paper presents a novel dynamic simulation tool able to assess and optimize the energy, environmental and economic performance of standard and innovative district heating/cooling systems. To this aim, several design and operating parameters (e.g.: weather conditions, heat selling price for users, national unitary price of electricity, etc.) are dynamically taken into account. The heating and cooling demands and loads of the buildings to be fed by the network working fluid are dynamically calculated. The system pipeline network is modelled through a suitable plug-flow approach. Fluid temperatures are calculated in each network node. The optimization of several system design and operating parameters is achieved for different objective functions. A suitable analysis is considered for selecting the most convenient urban zones for system application. The whole simulation model is implemented in a suitable computer code written in MatLab. By such tool useful design criteria and feasibility analyses can be obtained. To show the capabilities of the presented simulation tool, a novel case study, referred to a district heating system supplied by an existing thermoelectric power plant, was developed. The conducted analysis is based on system optimizations focused on the number of users, the selling heat/electricity prices and system geometric features. As for example, for minimizing the system payback to about 14.0 year, the optimal number of users and network length are 5 × 10 3 and 2.7 km, respectively. In this case the primary energy savings and the avoided carbon dioxide emissions are about 11.0 GWh/y and 16.1 ktCO2 /y, respectively.